Enhanced-Efficiency Randomized Response Model: A Simplified Framework - Ahmad M. Aboalkhair; El-Hosseiny, El-Emam; Mohammad A. Zayed; Tamer Elbayoumi; Mohamed Ibrahim; A. M. Elshehawey (Statistics, Optimization & Information Computing, 2025)
The key challenge in advancing randomized response techniques lies in enhancing efficiency while ensuring simplicity and ease of implementation. This research presents a fresh randomized response framework that achieves comparable effectiveness with fewer randomization devices, simplifying its real-world deployment. Compared to Aboalkhair’s (2025) model that depend on two randomization tools, the suggested method delivers equivalent efficiency with only a single tool. The study evaluates the new model’s superiority over existing approaches and establishes a measure of privacy protection. Through theoretical analysis and numerical comparisons, the results demonstrate distinct efficiency benefit of the suggested model.